Financial Restructuring in Conglomerates - Experience of Other Countries and Lessons for Vietnam - Hoang, My Linh; Nguyen, Manh Hung; Nguyen, Thi Ha (Archives of Business Research, 2025)
Financial restructuring plays a crucial role in ensuring the long-term stability and competitiveness of conglomerates, particularly in rapidly evolving economic landscapes. This study examines case studies from Spain, Italy, and South Korea to derive valuable lessons for Vietnamese conglomerates undergoing financial restructuring. The experiences of Jazztel, the Ferruzzi Group, Daewoo, and Hyundai highlight the importance of financial discipline, strategic debt restructuring, and corporate governance reform. In Vietnam, state-owned and private conglomerates are increasingly adopting restructuring measures, including debt restructuring, divestment from non-core assets, and digital transformation. Based on international case studies and Vietnam’s current restructuring efforts, this paper provides recommendations for Vietnamese conglomerates to enhance financial resilience, optimize governance structures, and ensure sustainable growth in an increasingly competitive global market.